Effect of tafamidis on global longitudinal strain and myocardial work in transthyretin cardiac amyloidosis. (11th March 2022) - Giblin, Gerard T; Cuddy, Sarah A M; González-López, Esther; Sewell, Alanna; Murphy, Amanda; Dorbala, Sharmila; Falk, Rodney H
Abstract: Aims: In patients with transthyretin amyloid cardiomyopathy (ATTR-CM), the effect of tafamidis on myocardial function using serial speckle tracking echocardiography has not been reported. The purpose of this study was to describe the natural history of myocardial function in untreated ATTR-CM and determine the effect of tafamidis on myocardial functional parameters over 12 months of treatment. Methods and results: A total of 45 subjects with ATTR-CM were retrospectively studied: 23 treated with tafamidis and 22 untreated. Two-dimensional speckle tracking echocardiography was analysed at baseline and 1 year. Serial longitudinal, circumferential, and radial strain, twist, torsion, and myocardial work were measured. Over 1 year, absolute global longitudinal strain (GLS) deteriorated more in the untreated group by a median of 1.1% [inter-quartile range (IQR) 0.95] compared with 0.3% (IQR 1) in the tafamidis group ( P = 0.02). Myocardial work index and efficiency also deteriorated to a greater degree: 142.5 mmHg% (IQR 197) and 4% (IQR 8), respectively, in the untreated group compared with 61.5 mmHg% (IQR 210) and 1% (IQR 7) in the tafamidis group ( P = 0.04). There were no significant between group differences in left ventricular ejection fraction (LVEF), tissue Doppler velocities, circumferential or radial strain, LV twist or torsion at 1 year. The stabilization effect of tafamidis on myocardial function at 1 year did not differ according to baseline GLS, LVEF, or National Amyloidosis Centre disease stage. Conclusions: In ATTR-CM, tafamidis resulted in a lesser deterioration in GLS, myocardial work index, and efficiency over a 12-month period compared with a cohort not treated with tafamidis. Graphical Abstract: